Problem Based Learning: Pengaruh Terhadap Pemahaman Konsep dan Komunikasi Siswa SMP - Widayanti Widayanti; Siti Anisatur Rofiqah; Trio Julianton (U-Teach: Journal Education of Young Physics Teacher, 2021)
This study aims to analyze the effect of the application of the problem-based learning (PBL) model on the conceptual understanding and communication skills of junior high school students. With a quasi-experimental method, this study used a multiple-choice test in the form of a four-tier and a communication questionnaire as a data collection technique. Data analysis using the mixed method. The research sample consisted of the experimental class and the control class. Based on the results of the statistical calculation of the t-test, it was found that tcount > ttable (12.61 > 1.67), then Ha was accepted. This shows that there is a significant effect of the problem-based learning (PBL) learning model on the ability to understand concepts of junior high school students. Meanwhile, from the results of the questionnaire calculation, the score of the experimental class was higher than the control class. So it can be concluded that student communication in the experimental class has a significant increase compared to the control class. Accordingly, the findings of this study indicate that PBL can improve the concept understanding and communication of junior high school students. Students who have high conceptual understanding tend to have good communication skills